2018
DOI: 10.1111/1754-9485.12747
|View full text |Cite
|
Sign up to set email alerts
|

Use of stereotactic body radiation therapy for oligometastatic recurrent prostate cancer: A systematic review

Abstract: The purpose of this study is to evaluate the effectiveness and safety of stereotactic body radiation therapy (SBRT) in the management of oligometastatic recurrent prostate cancer (PCa) by means of a systematic review. Six databases were searched (CENTRAL, Embase, LILACS, PubMed, Scopus and Web of Science). Additionally, hand-searching and grey literature search were performed. The main outcomes were progression-free survival (PFS) and toxicity rates. Androgen deprivation therapy-free survival (ADT-FS), local c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In prostate cancer, the argument of aggressive local treatments is supported by the recent finding that indolent metastatic lesions have the potential to transform and become aggressive foci of accelerated metastases ( 81 , 82 ). A recent systematic review summarized the use of SBRT for PET/CT proven oligometastatic prostate cancer ( 83 ). This study demonstrated excellent local outcomes, with no local recurrences when RT dose exceeded a biologically effective dose (BED) of >108 Gy (α/β = 3 Gy).…”
Section: Extrapelvic Oligometastatic Relapsementioning
confidence: 99%
“…In prostate cancer, the argument of aggressive local treatments is supported by the recent finding that indolent metastatic lesions have the potential to transform and become aggressive foci of accelerated metastases ( 81 , 82 ). A recent systematic review summarized the use of SBRT for PET/CT proven oligometastatic prostate cancer ( 83 ). This study demonstrated excellent local outcomes, with no local recurrences when RT dose exceeded a biologically effective dose (BED) of >108 Gy (α/β = 3 Gy).…”
Section: Extrapelvic Oligometastatic Relapsementioning
confidence: 99%
“…Several non-randomized studies and systematic reviews have shown a potential benefit of SABR treatment for oligometastatic disease in other solid tumours, such as breast, colorectal, lung and prostate. These studies have generally demonstrated that SABR for oligometastases yields high local control and may confer improved disease survival [25][26][27][28]. SABR-COMET was a phase II randomization between SABR and standard of care palliative radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous dose/fractionation schedules, inconsistent use of ADT, widespread dependence on conventional imaging and short follow-up complicate interpretation. This notwithstanding, a systematic review of 661 patients reported median PFS and ADT-free survival of between 1-3 years, excellent local control of 100% for tumours receiving a BED >108 Gy (α/β =3), and importantly, only 1 patient reported grade 3 acute toxicity (87). Data supporting SBRT in metachronous oligometastatic disease Accordant results were achieved in the POPSTAR trial, which evaluated the role of SBRT (20 Gy in 1 fraction) to up to 3 bone-only (n=20), node-only (n=12) or both (n=1) oligometastases (83).…”
Section: Early Datamentioning
confidence: 99%